BIP in global health: a multi-institutional blended intensive program for enhancing global health competencies - Alves Lopes, António; Casaca Carreira, João; Costa, D.; Badiola-Zabala, A.; Brottrager, B.; Wittkämper, D.; Molenaar, E.; Maric, F.; Kjønnerød, I. Fjell; van Wijchen, J.; Jokinen, K.; Nikolaisen, L. Johanne; et al. (My University, 2024)
Introduction: Blended Intensive Programs (BIP) in higher education combine short-term mobility with online collaboration, fostering innovative learning and teaching methods. These initiatives facilitate joint curricular development among students, academics, and staff in Higher Education Institutions (HEI) and empower students to develop innovative solutions to global health issues. This study evaluates the self-reported impact of a BIP designed to enhance students' understanding of global health and social challenges, with a focus on the Sustainable Development Goals. Methodology: Eight institutions from six countries collaborated to develop a two-month BIP aimed at enhancing health and social students' understanding of global health and social challenges. The program involved 12 teachers and 35 students. It was structured into three online sessions followed by an in-person week. The BIP covered key topics such as migrations, non-communicable diseases, climate change, and economic impacts on global health, with a strong emphasis on the Sustainable Development Goals. An online questionnaire, comprising Likert scale and open-ended questions, surveyed participants, gathering both quantitative data and qualitative feedback to provide a comprehensive overview of their experiences and learning outcomes. Results: Survey responses (n=25) were predominantly positive. The majority of participants agreed that the BIP increased their awareness and knowledge of global health and social problems, enhanced their understanding of the Sustainable Development Goals, and effectively facilitated understanding of their profession's role in global health issues. Participants appreciated the emphasis on multidisciplinary and interdisciplinary approaches. Teacher support during online and in-person sessions was positively rated. In terms of overall quality, the program received high ratings, with most participants rating it as "Very Good" or "Good." The recommendation rate was also high, with the majority of participants strongly agreeing or agreeing that they would recommend the BIP to other students. While most participants found the lectures and activities relevant, a minority indicated areas for improvement, particularly regarding the relevance of certain sessions. Conclusions: From the participants' perspective, the BIP successfully increased their understanding of global health challenges and the importance of collaborative and innovative approaches in addressing these issues. Despite some feedback on the relevance of certain sessions, the overall positive response suggests that BIPs can be an effective strategy in higher education to foster global awareness and problem-solving skills among students. This educational experience demonstrates the potential of BIPs as a valuable tool in higher education for developing students' global health competencies and promoting innovative solutions to complex challenges. However, the study's relatively small sample size and self-reported data may limit generalizability. Future research could explore long-term impacts of BIPs on students' career choices and contributions to global health initiatives, and benefit from larger sample sizes, longitudinal designs, and objective measures of learning outcomes.
Keywords: Blended intensive programs; Global health; Internationalization